If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x * 4 + -8x + 3 + 3x * 4 + -2x + 1 = 0 Reorder the terms for easier multiplication: 15 * 4x + -8x + 3 + 3x * 4 + -2x + 1 = 0 Multiply 15 * 4 60x + -8x + 3 + 3x * 4 + -2x + 1 = 0 Reorder the terms for easier multiplication: 60x + -8x + 3 + 3 * 4x + -2x + 1 = 0 Multiply 3 * 4 60x + -8x + 3 + 12x + -2x + 1 = 0 Reorder the terms: 3 + 1 + 60x + -8x + 12x + -2x = 0 Combine like terms: 3 + 1 = 4 4 + 60x + -8x + 12x + -2x = 0 Combine like terms: 60x + -8x = 52x 4 + 52x + 12x + -2x = 0 Combine like terms: 52x + 12x = 64x 4 + 64x + -2x = 0 Combine like terms: 64x + -2x = 62x 4 + 62x = 0 Solving 4 + 62x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 62x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 62x = 0 + -4 62x = 0 + -4 Combine like terms: 0 + -4 = -4 62x = -4 Divide each side by '62'. x = -0.06451612903 Simplifying x = -0.06451612903
| x^2-9x-67=0 | | -91=6y-15y-19 | | -8w+5(w-3)=-6 | | 2x+41+3x=6 | | -20=4v+8(v+2) | | -6w-7w-27=28 | | x^2-28x-288=0 | | -8=4(y+2)-8y | | 14=2u+6(u-3) | | 6(w+4)-4w=18 | | 2x^6+15x^3-8=0 | | X^3/x^2-9 | | 4ln((x/4)^2-1) | | -7(x-9)+7=70 | | 20x-8=40x+7 | | -3y-5y+10=36 | | 5x-15=250 | | 2-5(-1/2)= | | -0.3x+9.26=-0.7x+7.66 | | 8x-10=-10+3 | | 5(3x+9)=-41+26 | | 3(n+6)-(7n-4)=-5n | | 0.5x^2+100x-5000=0 | | 0.5x^2-100x+5000=0 | | 9(1+y)=8(y-6) | | x+17=7x+47 | | x^2+100x-10000=0 | | (x-15)(x-15)=-36 | | 15+17=-4(6x-8) | | 6(n+8)-(-4n-1)=9n | | 0=0+0 | | 15x-8=14x-12 |